2000
DOI: 10.1165/ajrcmb.22.6.3927
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-9 Upregulates Mucus Expression in the Airways

Abstract: Interleukin (IL)-9 has recently been shown to play an important role in allergic disease because its expression is strongly associated with the degree of airway responsiveness and the asthmatic-like phenotype. IL-9 is a pleiotropic cytokine that is active on many cell types involved in the allergic immune response. Mucus hypersecretion is a clinical feature of chronic airway diseases; however, the mechanisms underlying the induction of mucin are poorly understood. In this report, we show that IL-9 regulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
132
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(147 citation statements)
references
References 40 publications
(51 reference statements)
10
132
2
3
Order By: Relevance
“…This observation is consistent with the close association of mucous cell hyperplasia/metaplasia seen in allergic airway diseases such as asthma. IL-9 induces MUC5AC/Muc5ac both in vitro and in vivo (92)(93)(94)(95)(96), although few data exist as to the intracellular mechanisms of its action. IL-9's effect on MUC5AC may be mediated through IL-13 (95,96), although other studies dispute the role of IL-13 (92,94).…”
Section: Th2 Cytokines' Effects On Muc5ac: the Importance Of Injury Amentioning
confidence: 99%
“…This observation is consistent with the close association of mucous cell hyperplasia/metaplasia seen in allergic airway diseases such as asthma. IL-9 induces MUC5AC/Muc5ac both in vitro and in vivo (92)(93)(94)(95)(96), although few data exist as to the intracellular mechanisms of its action. IL-9's effect on MUC5AC may be mediated through IL-13 (95,96), although other studies dispute the role of IL-13 (92,94).…”
Section: Th2 Cytokines' Effects On Muc5ac: the Importance Of Injury Amentioning
confidence: 99%
“…IL-9 has also been shown to have the ability to stimulate mucous cell hyperplasia in vivo (35) as well as mucin gene expression in vitro (36,37). However, gene knockout mice of IL-9 showed that IL-9 was necessary for mucous cell hyperplasia in a granuloma model of disease (38) but not in an allergic asthma model (39).…”
mentioning
confidence: 99%
“…However, gene knockout mice of IL-9 showed that IL-9 was necessary for mucous cell hyperplasia in a granuloma model of disease (38) but not in an allergic asthma model (39). In cell cultures, stimulation of MUC5AC by IL-9 could be seen (36,37) but the cells used were undifferentiated TBE cells or cancerous cell lines. To further define the roles of cytokines in mucin gene expression, we used well differentiated primary cultures of human tracheobronchial epithelial (TBE) cells (40,41) to determine which cytokines can stimulate MUC5AC and MUC5B expression.…”
mentioning
confidence: 99%
“…Such conditions can be mimicked by overexpression of TH2 cytokines such as IL-9 and IL-13 in the lungs. Indeed, IL-9 transgenic (Tg) 3 and IL-13 Tg mice show increased mucus production by lung goblet cells (1,2) and airway hyperresponsiveness (2)(3)(4). Further studies of IL-9 Tg mice showed that IL-9 activities on lung epithelial cells are actually mediated by up-regulation of IL-13 expression by T and mast cells (5)(6)(7).…”
mentioning
confidence: 99%